Online System for Notifications on Appointments of Working Group Members: A Case Study of the Faculty of Agriculture and Technology, Rajamangala University of Technology Isan, Surin Campus - Srisuk, Supakorn; Pongsod, Phatpicha; Keawvongsa, Sutthilak; Chiawdee, Thammarong; Changkeaw, Lakkhana; Kongrasri, Sasicha; Sankla, Supadet; Kittichonthawat, Songyot; Sittiwong, Wuttichai (Academic Journal of Management Technology, 2022)
This article presents the development of an online system for notifications on appointments of working group members for the Faculty of Agriculture and Technology, Rajamangala University of Technology Isan, Surin Campus, and reports on the results of a user satisfaction survey with the developed system. The online system was created under the concept of systems development life cycle (SDLC), using MySQL, SQL commands, PHP, HTML, and JavaScript. The data were collected through the satisfaction questionnaire administered to 125 staff members from the Faculty of Agriculture and Technology, Rajamangala University of Technology Isan, Surin Campus, who were selected using purposive sampling method. The results showed that the online system developed by the researchers were evaluated by experts as being effective and easy to use. Moreover, results of the questionnaire showed that the system met the needs of the users and were perceived as having satisfactory functionalities and ease of use. In conclusion, the online system for notifications on appointments of working group members developed by the researchers is considered effective, user-friendly, and satisfactory by the experts and users. Therefore, the system may be applied for administering online notifications of official assignments within department effectively.